Select Birth Cohorts - Richard MacMinn; Frederik Weber (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2009)
Worldwide demographic changes and their implications for governments, corporations, and individuals have been in the focus of public interest for quite some time due to the fiscal risk related to adequate retirement benefits. Through a more detailed analysis of mortality data an additional type of risk can be identified: differences in mortality improvements by birth year, also known as "cohort effects." Previous contributions have, however, not formalized a suitable measure to further investigate mortality improvements but rather relied on graphical representations without particular focus on individual cohorts but groups of the overall population. No criterion to identify single birth year cohorts as select has been established. A simple criterion for identifying select cohorts is proposed and used here to what country mortality data reveals about the mortality and longevity experience of cohorts. Select cohorts are rare but can be quite different from surrounding cohorts and so may generate financial risks that need to be hedged naturally or artificially with new ART instruments.
urn:nbn:de:bvb:19-epub-9207-4
Keywords: I12; J1; N3; 650; mortality improvement; longevity trend; select cohort; longevity risk; Demographie; Sterblichkeit; Fertilität; Kohortenanalyse; Welt